2008
DOI: 10.1529/biophysj.107.120717
|View full text |Cite
|
Sign up to set email alerts
|

Experimental and Computational Studies Investigating Trehalose Protection of HepG2 Cells from Palmitate-Induced Toxicity

Abstract: Understanding the mechanism of saturated fatty acid-induced hepatocyte toxicity may provide insight into cures for diseases such as obesity-associated cirrhosis. Trehalose, a nonreducing disaccharide shown to protect proteins and cellular membranes from inactivation or denaturation caused by different stress conditions, also protects hepatocytes from palmitate-induced toxicity. Our results suggest that trehalose serves as a free radical scavenger and alleviates damage from hydrogen peroxide secreted by the com… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
38
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(48 citation statements)
references
References 105 publications
(112 reference statements)
10
38
0
Order By: Relevance
“…The compatibility of the present (and previous experimental [5,9,7,[19][20][21][22][23][24][25][26][30][31][32][33][34][35][36][37][38][39][40][44][45][46][47][48][49][50][51][52][53][54][55][56][57][58][59][60] and computational [41][42][43][63][64][65][66][67][68][69][70][71][72]) observa...…”
Section: Resultssupporting
confidence: 66%
See 1 more Smart Citation
“…The compatibility of the present (and previous experimental [5,9,7,[19][20][21][22][23][24][25][26][30][31][32][33][34][35][36][37][38][39][40][44][45][46][47][48][49][50][51][52][53][54][55][56][57][58][59][60] and computational [41][42][43][63][64][65][66][67][68][69][70][71][72]) observa...…”
Section: Resultssupporting
confidence: 66%
“…In the case of membranes, the simulations [29,[41][42][43][63][64][65][66][67][68][69][70][71][72] systematically revealed a preferential affinity of the sugar molecules for the bilayer surface and a direct interaction (through H-bonds) with the lipid headgroups, even in dilute solutions, providing support for the WRH (possibly along with [29,[41][42][43] the HBH). In contrast, in the case of proteins, the simulations [51,53,57,54,56,[73][74][75][76][77] rather suggested a preferential exclusion of the sugar molecules from the biomolecular surface (trapped water layer), even in concentrated solutions, providing support for the WEH (along with the VIH for concentrated sugar solutions [74]).…”
Section: Introductionmentioning
confidence: 99%
“…A slight elevated levels of neutrophills and monocyte was also found but, these values were in normal laboratory range. Some researchers have demonstrated that corticosteroids treatment causes the neutrophils to detach from endothelial cells of blood vessels and inhibit the rate of removal from vascular compartment [23] and apoptosis of neutrophils [24]. At the same time, lymphocyte count reduced in dose dependant manner in drug treated animals.…”
Section: Effect Of Dexamethasone Palmitate On Haematological Parametersmentioning
confidence: 99%
“…Several of the natural health products have been associated with hepatotoxicity; however, much of the information about these associations is from studies done on animals or in vitro, and precise dosage information is limited. [4][5][6][7][8][9][10][11][12]15 Both venlafaxine and varenicline have been reported to cause hepatotoxicity in patients, especially in those with underlying liver conditions. [1][2][3] Tables 1 and 2 provide summaries of the patient's medications and any published evidence of hepatotoxicity associated with their use.…”
Section: Discussionmentioning
confidence: 99%
“…Over the past three months, she had been taking six prescription medications (Table 1) 1-3 and seven natural health products (Table 2). [4][5][6][7][8][9][10][11][12] Her bilirubin level had been elevated (281 [normal 3.4-22] µmol/L), as had her liver enzyme levels (alanine transaminase 755 [normal ] U/L and alkaline phosphatase 273 [normal 42-98] U/L). An ultrasound of her abdomen had been consistent with cirrhosis, and the presumptive diagnosis had been cirrhotic liver disease.…”
mentioning
confidence: 99%